A Zincke aldehyde approach to gelsemine. Issue 23 (3rd June 2015) - Lam, Jonathan K.; Joseph, Scott B.; Vanderwal, Christopher D.
Graphical abstract: Abstract: We have developed a Zincke-aldehyde-based approach to the complex alkaloid gelsemine. It features a key thermal pericyclic cascade that converts a Zincke aldehyde bearing a pendant alkene into a hydroisoindolone product that shares many structural features with the target molecule. Our efforts to convert these intermediates to gelsemine are also discussed.